Forefoot Pain in the Lesser Toes: Anatomical Considerations and Magnetic Resonance Imaging Findings. Issue 4 (November 2019) - Hulstaert, Tine; Shahabpour, Maryam; Provyn, Steven; Lenchik, Leon; Simons, Philip; Vanheste, Ruben; De Maeseneer, Michel
Various conditions may result in forefoot pain. Magnetic resonance (MR) imaging allows accurate assessment of many of these conditions. We provide an overview of forefoot disorders divided into bones, capsule and plantar plate, musculotendinous structures, neurovascular structures, and subcutaneous tissue. We review normal anatomical features as well as MR imaging findings of common disorders.